(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
To the present day, bioethanol is considered to be a perspective substance, which can serve as fuel for cars and replace petroleum products. Therefore a lot of experiments on ways of bioethanol production, its further use as an organic gasoline substitute are carried out. However in our country these developments are limited and in the basis of the study are such substances as starch and sugar. But it can be assumed that the use of ordinary cane will be more cost-effective and therefore persepective direction of biofuel production